Model Komunikasi Kyai di Perguruan Tinggi - Iwan Kuswandi (IAIN Padangsidimpuan, 2019)
The higher education and pesantren are two of education traditions that have many deversity. In pesantren, Kyai (moslem scholars) are the figure who have domain role, it is different in higher education that has formal organization where has structural, fungsional, and bureaucracy well, it doesn’t depend on one figure only. Kyai (Moslem scholars) are the first component of communication in pesantren. In this times, there are many pesantren established the higher education, in other sides, they are also hope as the head of higher education. This study analysis deeper of what are the Style of communication that is used by Kyai (Moslem scholars) in pesantren of Institut Dirosat Islamiyah Al-Amien (IDIA) Prenduan Sumenep. This campus is pesantren campus in around of Pesantren Al-Amien Prenduan. It result is covered that the Style of communication are: the Style of communication is one direction, the Style of interactive communication, the Style of transaction communication, the Style of transmission communication, the Style of ritual and expressive communication, the Style of publicity communication, and the Style of reception communication.